H∞ Formation Control and Obstacle Avoidance for Hybrid Multi-Agent Systems - Dong Xue; Jing Yao; Jun Wang (Journal of Applied Mathematics)
A new concept of H∞ formation is proposed to handle a group of agents navigating in a free and an obstacle-laden environment while maintaining a desired formation and changing formations when required. With respect to the requirements of changing formation subject to internal or external events, a hybrid multiagent system (HMAS) is formulated in this paper. Based on the fact that obstacles impose the negative effect on the formation of HMAS, the H∞ formation is introduced to reflect the above disturbed situation and quantify the attenuation level of obstacle avoidance via the H∞-norm of formation stability. An improved Newtonian potential function and a set of repulsive functions are employed to guarantee the HMAS formation-keeping and collision-avoiding from obstacles in a path planning problem, respectively. Simulation results in this paper show that the proposed formation algorithms can effectively allow the multiagent system to avoid penetration into obstacles while accomplishing prespecified global objective successfully.